If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6 = 8(x + -4) Reorder the terms: 6 + 7x = 8(x + -4) Reorder the terms: 6 + 7x = 8(-4 + x) 6 + 7x = (-4 * 8 + x * 8) 6 + 7x = (-32 + 8x) Solving 6 + 7x = -32 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6 + 7x + -8x = -32 + 8x + -8x Combine like terms: 7x + -8x = -1x 6 + -1x = -32 + 8x + -8x Combine like terms: 8x + -8x = 0 6 + -1x = -32 + 0 6 + -1x = -32 Add '-6' to each side of the equation. 6 + -6 + -1x = -32 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = -32 + -6 -1x = -32 + -6 Combine like terms: -32 + -6 = -38 -1x = -38 Divide each side by '-1'. x = 38 Simplifying x = 38
| 45+5n=10(8n-2)-10n | | 5x+7(x-14)=5(x-14) | | 10(2n-3)=(10n+6)+4 | | y=3x^2-4x-6 | | 36-25x^2=0 | | y=x^2-6 | | 3x+12=7*3 | | 4x+(x-9)=4(x-10) | | 6(3n-5)=(9n+8)+5 | | ax+2=aw | | 4=t-5s | | 5n-8=-48 | | (x^3+4x^2)-(2x-8)=0 | | 3n-9=-27 | | 3-6(4+8n)=-21+10n | | 20r^2-41r+20=0 | | x(10x+24)=0 | | (s+16)(s+81)=0 | | 7-3x=15+5x | | 3-6(4+8n)=21+10n | | c(c+3)=0 | | y-(2y-5)=94 | | (3s+7)(s+6)=0 | | (3)-(-4)= | | s^2+11s+24=0 | | c^2-11c+18=0 | | 4x-7=3.5 | | -4(t+2)=12 | | s^7-7s=0 | | 32-14=3(x-4) | | -29+7x=-5(1-2x) | | 12x=6x+24 |